(untitled) (GEON Journal (Management, Organizations and Business), 2018)
This article deals with the International Auditing Standard (ISA) 220 that relates to the Quality Control of the Audit of Financial Statements, which establishes the specific responsibilities of the firm’s personnel regarding quality control procedures for audits of historical financial information. Its objective was to identify the knowledge that the Public Accountants of the city of Villavicencio have of the International Auditing Standard (NIA) 220 that relates to the Quality Control of the Audit of Financial Statements. The method used was quantitative, through which the information obtained from Public Accountants of the Universidad Cooperativa de Colombia, Villavicencio Headquarters was analyzed, obtaining as a result that there is ignorance on the part of the Public Accountants who act as External Auditors, especially in the responsibilities that has the Work Partner within his team, so it is concluded that this ignorance of the rule prevents him from taking responsibility for the overall quality of the work carried out by his company.